Drive Bersama Dalam Pemaksimalan Penggunaan Akun Belajar.Id untuk Memantau Kegiatan di Sekolah Binaan - Fadilah, Haris (ANTHOR: Education and Learning Journal, 2022)
Every public and private school is required to make and have a complete and neatly storedadministration, because every 5 years, every educational unit must be accredited through theNational Accreditation Board (BAN). This accreditation activity aims to determine thefeasibility of an educational institution with the standards set by the government. To store allschool administration, both administration created or managed by the school principal andall administration created or managed by all teacher boards. All administration of extracurricular activities as well as administration of all activities carried out by external parties that have been attended by the school. So that all of these administrations are stored neatly, in the current era of technological advances and the access that has been provided by the government, especially for the world of education, in the form of a "learning. id account", the school has the opportunity to save all school administration in the "drive" that is in learning.id account. Schools make joint drives for school principals, teachers, and education staff which can be accessed by development supervisors to see the activitiescarried out by the target schools.